Evaluasi Koefisien Tanaman Padi Berdasarkan Konsumsi Air pada Lahan Sawah - Hanhan Ahmad Sofiyuddin; Lolly M. Martief; Budi Indra Setiawan; Chusnul Arif (Balai Teknik Irigasi, 2012)
Crop coefficient was calculated based on the observation of water consumption of various treated paddy fields on the objective to find its changes with time as the plant grew. Three principal techniques of paddy fields known as System of Rice Intensification, Integrated Crop Management and commonly practiced were investigated. Each of them has major different in irrigating and planting patterns, which lead to different performance on plant growth, productivity and water consumption. In this study, the combinations of irrigating and planting patterns across these 3 systems investigated. Measurements were conducted in daily basis on water level, perched water table, irrigation water, drainage water and weather parameters. Water balance analysis was carried out to calculate equivalent depth of soil water storage, which was then compared with measured soil water storage based on water level data and soil water retention curve. The results showed that each treatment produced similar crop coefficients. Average crop coefficient in 15 days periods are 0,87, 1,03, 1,13, 1,24, 1,28 and 1,25. These values are important to understand more about water saving mechanism as an input to develop irrigation discharge planning standard.